Concepts of Administrative Court Proceedings - Yangiboyev, Norkuvvat; Umidullayev , Asilbek; Olimov , Maxmayusuf (WORLD INTERNATIONAL CONFERENCE ON SCIENCE, TECHNOLOGY AND EDUCATION, 2026)
This article analyzes the legal foundations, formation process, and development stages of administrative court proceedings in the Republic of Uzbekistan, as well as their role within the judicial system. It substantiates that the establishment of administrative courts is aimed at ensuring the effective resolution of disputes arising between individuals or legal entities and state bodies, as well as protecting their rights and legitimate interests through judicial mechanisms. The article also examines large-scale judicial and legal reforms implemented in the country, including the Action Strategy for further development and subsequent normative legal acts. It emphasizes that the introduction of administrative courts strengthens judicial control over public authorities and improves citizens’ access to fair justice. Furthermore, the study highlights institutional reforms This article analyzes the legal foundations, formation process, and development stages of administrative court proceedings in the Republic of Uzbekistan, as well as their role within the judicial system. It substantiates that the establishment of administrative courts is aimed at ensuring the effective resolution of disputes arising between individuals or legal entities and state bodies, as well as protecting their rights and legitimate interests through judicial mechanisms. The article also examines large-scale judicial and legal reforms implemented in the country, including the Action Strategy for further development and subsequent normative legal acts. It emphasizes that the introduction of administrative courts strengthens judicial control over public authorities and improves citizens’ access to fair justice. Furthermore, the study highlights institutional reforms within the judicial system, improvements in procedural mechanisms, and measures aimed at safeguarding human rights. Special attention is given to strengthening judicial independence, enhancing transparency, and ensuring equality of parties in court proceedings. within the judicial system, improvements in procedural mechanisms, and measures aimed at safeguarding human rights. Special attention is given to strengthening judicial independence, enhancing transparency, and ensuring equality of parties in court proceedings.